The Impact of Television Advertising on Children Buying Behaviour in Chocolate Market Sri Lanka - Herath, H.M.W.M.; Kapilarathana, A.G.K (International Journal of Social and Administrative Sciences, 2019)
The main purpose of this study was to identify the impact of Television Advertising on Children Buying Behavior in the chocolate market in Sri Lanka. The data was gathered from 150 respondents in Kurunegala district in Sri Lanka using multistage sampling technique. SPSS software package was used to analyze the data. It was found that most of the children in 6-10 age in Sri Lanka watch television more than 3 hours per day. And they also watch advertisement during the period. Most of the children willing to purchase and consume Ritzbury Chocolate among several chocolate brands in the Sri Lankan market. According to the findings, the most significant television advertising dimension is Information focused advertising. In addition to that, it was found that the Emotion-focused and Imagery focused advertising also significantly influence on children buying behavior in the chocolate market. The study concluded a positive relationship between Television Advertising and Children Buying Behavior.